Negative indefinites - Penka, Doris (Oxford : Oxford University Press, 2011)
Doris Penka delivers a unified analysis of the semantics and syntax of negative indefinites - as in the expressions nobody nothing, never and nowhere - and their counterparts in other languages. Contrary to standard assumptions, the author argues that these expressions are not inherently negative and are only licensed by a covert negation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Definiteness (Linguistics); Grammar, Comparative and general -- Negatives; Grammar, Comparative and general -- Determiners; Semantics